Centro de memórias feministas implantado em Palmas-TO - Leite, Vívian Albuquerque (Universidade Federal do Tocantins, 2020)
This final paper consists in the develping an architectue proposal capable of creating a spot at the service of the population, creating awereness and breaking any negative barriers, that discrimination and the lack of information, together, build arround our society, especially regarding feminist themes. The locus established for the implemetation of the Feminist's Memories Center will be at the Girassois square located in th very center of Tocatins capital, since it's a big historical and urban planning landmark of municipality. According the author, Palmas - the capital- shows, not be worried with preserving its history, bearing in mind that in 2017, a historic building, that once was head office of the Legislative Assembly, was hit by a arson fire. In an attempt to bypass the problems presented above, this paper, proposes a project in a provileged and widely used by city residents for physical exercise, such as jogging, yoga and evening laisures; above all that, there has a Cathedral, wich may attract some audience concerned in get to know the new space of cultural lasure. The bond between the Catholic Church and Feminism have always a disciplining role, sometimes against the feminism, and sometimes in favor. That means, the paradoxical relationship of religious organized institutions and the society, along with the purposes of feminist movement, make possible that the issues presented in this academic research, leaves, the academic enviroment, and begin to make shape in an everyday life. Is necessary discuss about feminism and show that is possible to have a healthy dialogue with society, beign culture the key element to achieve this goal.